2015
DOI: 10.1590/0104-07072015001130014
|View full text |Cite
|
Sign up to set email alerts
|

The role of family relations, spirituality and entertainment in moderating peer influence and drug use among students of eight universities from five countries in Latin America and three from the Caribbean

Abstract: This study is a multi-centric investigation on the role of family relations, spirituality and entertainment in moderating the relationship between peer influence and drug use (licit and illicit) among students from eight universities from five countries in LatinAmerica and three from the Caribbean. The sample was composed by 2198 university students from faculties of Social Sciences and Humanities/Health Sciences. Drug use was the dependent variable and the level of peer influence (number of friends who use dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
(9 reference statements)
0
13
0
2
Order By: Relevance
“…Thus, there are difficulties to meet the needs of this group fully. 2 The drug problem has intensified in all social classes, 3 establishing a challenge, especially with regard to the formulation and proposal of public policies and coping strategies to deal with this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there are difficulties to meet the needs of this group fully. 2 The drug problem has intensified in all social classes, 3 establishing a challenge, especially with regard to the formulation and proposal of public policies and coping strategies to deal with this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies show that entering university is a facilitating event to access drugs. 3 The new experiences that arise in social gatherings and the length of stay away from the family make the young person more vulnerable. 6,10 Added to these factors are the conflicts related to transition to adulthood including psychological factors, family relationships, 1 peer pressure, religion, 3 and economic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 This study suggests that differences in knowledge about the effects of alcohol and alcohol may exist based on the configuration of the university (traditional versus non-traditional) that reinforce the only relationship of dependence found in this study between the consumption of drugs and the socio-demographic variable related to the importance of religious beliefs, that is, there is less likelihood that one will consume drugs regarding larger importance to religious beliefs of the interviewed college student. 13 The data obtained by this study will be used for preventing, intervening and developing public policies. These initiatives are especially important for university students, who are under risk -depending on their stage of development as young adults and their social stage -as they begin to be independent.…”
Section: /12mentioning
confidence: 99%
“…Some studies have reported increases in marijuana use corresponding to a change in the legal environment for medical marijuana. [42][43][44] In the current study, marijuana was not made legal for adolescents and the law had not been implemented at the time of data collection. However, in the light of present realities, where marijuana has now been decriminalized in Belize, there is need for a follow-up study to examine the risk perceptions of adolescents within current framework of changed marijuana policy.…”
Section: /14mentioning
confidence: 99%